Implementation Of Differentiated Learning Using Canva and Quipper to Improve Learning Outcomes in Trigonometry Material - Chiarun Nisa, Nenden (International Journal of Geometry Research and Inventions in Education, 2024)
This research is a classroom action research that pays attention to learning styles, namely visual, auditory, and kinesthetic learning styles. This study aimed to determine the implementation of differentiated learning assisted by Canva and Quipper media to improve learning outcomes of class XI IPA 4 in trigonometry material so that the improvement can be known. This classroom action research was carried out in September-October 2023 with two cycles. In cycle I, differentiated learning was carried out with 75% student activity. The test results in cycle I showed completeness of 58.62%, with an average of 80.82. Because it has not met the benchmark for success, an increase is needed in cycle II with changes in strategies in the kinesthetic group and visual group from cycle I. In cycle II, differentiated learning was carried out with 87.5% student activity. The test results in cycle II increased with a completeness percentage of 88.23%, with an average of 89.67. The results of cycle II have met the criteria for class learning completion so the application of differentiated learning on trigonometry material in class XI IPA 4 is said to be successful. Differentiated learning assisted by Canva and Quipper can be one of the learning strategies chosen